The Relationship of Education and Parity With Kangaroo Care Method at Room Tebing Tinggi Hospital Perinatology Year - Vellyza Collin; Buyung Keraman; Damayanti Damayanti (Jurnal Sains Kesehatan, 2018)
One of indicators in the successful health affair in a country is the number of infant mortality rate. Causes of mortality among others are respiratory disorders 37%, prematurity 34%, sepsis 12%, hypothermia 7%, post mature 3% and congenital defect 1% and blood defect or icterus 6%. Infant mortality due to hypothermia can be prevented by practical method as an alternative to incubator namely Kangaroo Care Method. The implementation of Kangaroo Care Method must be monitored and evaluated by health care provider especially the ners. This research aims to study the relationship between education and parity with kangaroo care method in Tebing Tinggi Hospital Perinatology Space Year in 2017. This research uses descriptive design korelational with the approach of cross sectional study design. The population in this studyall infants born with low birth weight in room Tebing Tinggi Hospital Perinatology In 2017 there were 42 babies using total sampling. Collecting data in this study by looking at the data dukementasi using univariate and bivariate analysis using statistical test Chi-Square Test and Contingency Coefficient (C). The results showed: of the 42 respondents there were 25 people (61.9%) did not do kangaroo care method, 23 people (54.8%) with primary education, 27 people (64.3%) with parity primiparous, there is a significant relationship between education and care in the kangaroo method Tebing Tinggi Hospital Perinatology Space Year in 2017 with a close relationship category, and there is a significant relationship between parity with the treatment method of kangaroos in Space Perinatology General Hospital Tebing Tinggi Year 2017, with the category of close relationship.  Keywords: education, kangaroo care, parity